Pakistan’s First National Security Policy 2022-2026: The Analysis of Security Compulsions and Objectives (Al-NASR, 2024)
Security and stability are always been an integral aim of human life so is the case with states. A state’s security paradigm is a determined or undetermined path to make its survival possible depending on the environment it is interacting. Pakistan’s security path is also determined by the environment it was interacting. It made alliances with West at times to enhance its hard-core national security but after 9/11 a drastic change was observed. Pakistan reconsidered its national security policy by focusing on the soft core of its national security path. The aim of writing this article is to see what factors led Pakistan to transform its focus from hard core to soft core of national security and its path to formulate its first national security policy 2022-2026. This article also elaborates the past national security directives of the state along with the national security compulsions it is facing. Thus, this article gives a detailed overview or genesis of Pakistan’s first national security policy 2022-2026 along with its shortcomings.
Keywords: National Security; Military Security; Soft Security; Hard Security; Security Compulsions; Environmental Ethics